KONTRIBUSI SURAT KABAR LOKAL DIY DALAM PENYEBARAN INFORMASI INOVASI PERTANIAN - , MESALIA KRISKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to: (1) identify the presentation of agricultural news that includes information on agricultural innovations and, (2) compare the content/information related to agricultural innovation. So, by knowing both, may give preference to the readers about what local newspaper that can give them informatin of agricultural innnovation that is compatible with their needs. The research took sampling in 4 local newspapers in DIY and surrounding, they are SKH (Surat Kabar Harian/Daily Newspaper) Kedaulatan Rakyat, SKH Berita Nasional (BERNAS), SKH Radar Jogja, dan SKH Tribun Jogja. The basic method used in this research was comparative descriptive method, combining content analysis and discourse analysis applied by van Dijk technique. Sampling was done purposively, newspaper in the period of January- April 2013, with 4 samples in each month for every newspapers. The discourse analysis was taken regarding to news topics âthe rising of garlic priceâ. To test the hypothesis, it used One-Way Analysis of Variance. The presentation of innovation news can be divided into four, namely technological innovation, agricultural policy innovation, institutional innovation, and marketing innovation. The results showed that the order of presentation of the agricultural innovation that contributes greatly were SKH Kedaulatan Rakyat, SKH BERNAS, SKH Tribun Jogja, and SKH Radar Jogja, with the presentation of more noninnovation news, local news and the dominance of government. The most presentation of material scope was technological innovation. Discourse analysis about âthe rising of garlic priceâ was done only in 3 newspapers, KR (publish 3 news), Bernas (publish 2 news), and Tribun (publish 1 news), while Radar didnât publish any news. Though they presented in different intensity, over all the presented of the news were good,fulfilled the way of news presenting, and impartial.